The Characterization of A Thermoelectric Generator Type TEC1-12706 Hybridized On 50W Polycrystalline PV - Iskandar Iskandar; Arif Rahman Hakim; Mustofa Mustofa; Rustan Hatib; Yuli Asmi Rahman; Zuryati Djafar; Wahyu Haryadi Piarah (Jurnal Ecotipe (Electronic, Control, Telecommunication, Information, and Power Engineering), 2024)
The potential of solar energy is very large in generating electrical energy conversion using TEG and PV technology. Therefore, it is important to understand how the technology works. This study aims to characterize the electrical generation of 12 TEG modules type TEC1-12706 hybridized with 2 PV panels. One PV panel is left without a TEG module as a comparison. Meanwhile, on the cold side of the TEG attached to the PV, a heatsink with 3 fins is placed. The left and right fins are air allowed to flow naturally, while the middle fin is flowed with cold water fluid through a 0.01 m diameter water hose with 2 flow rates; 0.02 and 0.05 m / s. The results of the study showed that the fluid flow rate of 0.02 presented a better TEG performance effect than 0.05 m / s at an irradiance of 450 W/m2. Different things are shown by PV solar panels, where the power generation and efficiency are better in TEG at a flow rate of 0.05 m/s compared to 0.02 m/s for the same irradiance. Overall, the performance of PV-TEG is better at a TEG cooling fluid flow rate of 0.05 m/s.